2021
DOI: 10.1002/aah.10143
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of an Optimal Protocol for Contrast‐Enhanced Micro‐Computed Tomography in the Cloudy Catshark Scyliorhinus torazame

Abstract: The purpose of this study was to determine the optimal imaging protocol for contrast‐enhanced computed tomography (CECT) using micro‐CT (μ‐CT) for the posterior cardinal vein (PCV), dorsal aorta (DA), hepatic portal vein (HPV), kidney, liver, cephalic arteries (CAs), and gills of Cloudy Catsharks Scyliorhinus torazame. Additionally, we examined the availability of CECT screening for the coelomic organs. Different doses of iopamidol (100, 300, 500, and 700 mg iodine [mgI]/kg) were administered intravenously for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…However, among the parenchymal organs, the liver had a low signal enhancement of 17.56 HU. This is in agreement with a study that found that the signal enhancement of the liver of a cloudy catshark ( Scyliorhinus torazame ) did not increase as expected in mammals, because the fat vacuoles in the liver impeded the inflow and circulation of contrast medium (Ito et al, 2021). In contrast, the signal enhancement was significantly higher (19.17 HU) in the lumen of the seminal vesicle, which was higher than the signal enhancement in the liver.…”
Section: Disucussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, among the parenchymal organs, the liver had a low signal enhancement of 17.56 HU. This is in agreement with a study that found that the signal enhancement of the liver of a cloudy catshark ( Scyliorhinus torazame ) did not increase as expected in mammals, because the fat vacuoles in the liver impeded the inflow and circulation of contrast medium (Ito et al, 2021). In contrast, the signal enhancement was significantly higher (19.17 HU) in the lumen of the seminal vesicle, which was higher than the signal enhancement in the liver.…”
Section: Disucussionsupporting
confidence: 92%
“…After the anaesthetised sharks were examined using the NCCT scan for ~1 min, they were returned to the tank for sufficient oxygenation. Based on the results of a previous study (Ito et al, 2021), iopamidol (Oypalomin; Fuji Pharma) with an iodine concentration of 700 mg/kg was administered manually for 20 s via the caudal vein. A CECT scan was performed 30 min after administration of contrast medium.…”
Section: Methodsmentioning
confidence: 99%